Editorial: Clinical Implications of Diagnosing Irritable Bowel Syndrome: Do All Roads Need to Lead to Rome?. (June 2017) - Keszthelyi, Daniel; Ringel, Yehuda
Abstract : Abstract: : Irritable bowel syndrome (IBS) is one of the most common diagnoses made by healthcare providers. Yet the majority of patients with IBS are undiagnosed. The study by Sayuk et al. allows insight into the characteristics of different patient groups, e.g., with and without a formal diagnosis of diarrhea predominant IBS (IBS‐D). We discuss the questions raised by this study regarding the importance of making a confident diagnosis, conveying it to patients and their implications for clinical practice.